High-frequency neural oscillations and visual processing deficits in schizophrenia - Tan, Heng-Ru May; Lana, Luiz; Uhlhaas, Peter J. (Frontiers in Psychology, 2013)
Visual information is fundamental to how we understand our environment, make predictions and interact with others. Recent research has underscored the importance of visuo-perceptual dysfunctions for cognitive deficits and pathophysiological processes in schizophrenia. In the current paper, we review evidence for the relevance of high frequency (beta/gamma) oscillations associated with the visuo-perceptual dysfunctions in schizophrenia. In the first part of the paper, we examine the relationship between beta/gamma band oscillations and visual processing during normal brain functioning. We then summarize studies employing EEG/MEG which demonstrate reduced amplitude and synchrony of high-frequency activity during visual stimulation in schizophrenia. In the final part of the paper, we identify neurobiological correlates as well as offer perspectives for future research to stimulate further inquiry into the role of high-frequency oscillations in visual processing impairments in the disorder.